ECTRIMS/EAN guideline on the pharmacological treatment of people with multiple sclerosis. (19th January 2018) - Montalban, X.; Gold, R.; Thompson, A. J.; Otero‐Romero, S.; Amato, M. P.; Chandraratna, D.; Clanet, M.; Comi, G.; Derfuss, T.; Fazekas, F.; Hartung, H. P.; Havrdova, E.; et al.
Abstract : Background and purpose: Multiple sclerosis (MS) is a complex disease with new drugs becoming available in the past years. There is therefore a need for a reference tool compiling current data to aid professionals in treatment decisions. The objective was to develop an evidence‐based clinical practice guideline for the pharmacological treatment of people with MS. Methods: This guideline has been developed using the GRADE methodology and following the updated EAN recommendations for guideline development. Clinical questions were formulated in PICO format (patient, intervention, comparator, outcome) and outcomes were prioritized according to their relevance to clinical practice. Literature searches up to December 2016 were performed and the evidence is presented narratively and, when possible, combined in a meta‐analysis. The quality of evidence was rated into four categories – very high, high, low and very low − according to the risk of bias. The recommendations with assigned strength (strong, weak) were formulated based on the quality of evidence and the risk−benefit balance. Consensus between the panelists was reached by use of the modified nominal group technique. Results: A total of 10 questions have been agreed, encompassing treatment efficacy, response criteria, strategies to address suboptimal response and safety concerns and treatment strategies in MS and pregnancy. The guideline takes into account all disease‐modifying drugs approved by the European Medicine Agency at the time of publication. A total of 21 recommendations were agreed by the guideline working group members after three rounds of consensus. Conclusion: The present guideline, which includes descriptions of the evidence together with recommendations, will enable homogeneity of treatment decisions across Europe.